ITKAS public intellectual knowledge centre - Mohd Zaki, Ahmad (2021)
PEKAN, 12 March 2021 - The establishment of the Institute of Civilisation and Strategic Studies (ITKAS), Universiti Malaysia Pahang (UMP) is one of the shifts in the formation of the university ecosystem that can optimise the existence of UMP in Pahang.